Preparation of Photocatalytic Films from Recycled High-Density Polyethylene Using Black-Tio2 and Black-Tio2/Ag Nanoparticles Towards Nox Abatement - Carbonnel-Torralbo, A; Herrera-Diaz, F; Herrera-Diaz, F; Ibacache-Rojas, J; Zapata-Ramirez, P; Gavilanes-Ruiz, D; Saavedra-Gonzalez, M (Korean Society of Industrial Engineering Chemistry, 2026)
Novel films from recycled high-density polyethylene (HDPEr) were decorated with two photocatalysts: black TiO2 (B-TiO2) and Ag-loaded black TiO2 (B-TiO2-Ag). B-TiO2 synthesis and Ag deposition were achieved through chemical reduction of their respective precursors. The films were prepared via extrusion and compression molding, with two photocatalyst incorporation methods evaluated: direct addition during extrusion and film immersion into aqueous photocatalyst suspensions, including plasma pre-treatment. The latter introduced polar functional groups, enhancing nanoparticle adhesion to the film surface. Results confirmed successful Ag deposition on B-TiO2 via chemical reduction, with anatase reduction using NaBH4 increasing Ti3+ sites. Interestingly, two oxidation states of Ag were detected in B-TiO2-Ag. However, nanoparticle aggregation occurred during extrusion, likely due to poor compatibility between the polymer matrix and nanoparticles in terms of hydrophilicity, which plasma treatment mitigated. Regarding mechanical properties, nanoparticle incorporation via extrusion improved the Young’s modulus. Moreover, plasma-treated films exhibited significantly enhanced photocatalytic activity, leading to NOx abatement. In standardized tests, films with B-TiO2 and B-TiO2-Ag achieved NOX removal rates of 30.17 % and 40.80 %, respectively. This innovative approach valorizes HDPEr, offering a sustainable strategy for developing building materials that contribute to atmospheric pollution reduction. © 2025 The Korean Society of Industrial and Engineering Chemistry.